2015
DOI: 10.1055/s-0035-1566226
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Triple-Region Spinal Stenosis Treated with Simultaneous Surgery: Case Report and Review of the Literature

Abstract: Study Design Case report. Objectives Symptomatic triple-region spinal stenosis (TRSS), defined as spinal stenosis in three different regions of the spine, is extremely rare. To our knowledge, treatment with simultaneous decompressive surgery is not described in the literature. We report a case of a patient with TRSS who was treated successfully with simultaneous decompressive surgery in three separate regions of the spine. Methods A 50-year-old man presented with combined progressive cervical and thoracic myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
5
0
4
Order By: Relevance
“…На основании комплексной оценки анатомических, клинических и инструментальных параметров авторы разработали алгоритм тактики хирургического лечения пациентов с тандем-стенозами шейного и пояснично-крестцового отделов позвоночника, базирующийся на факторах, которые влияют на клинический исход: анамнестических данных (длительности заболевания), особенностях принятой хирургической тактики (первичности отдела позвоночника при вмешательстве, объеме декомпрессии, периоде между этапами операций). При анализе данных современной литературы установлено, что большинство исследований о результатах лечения пациентов с тандем-стенозами позвоночного канала являются ретроспективными [13,17,21,22] или описывают отдельные клинические случаи [12,23,24].…”
Section: Discussionunclassified
“…На основании комплексной оценки анатомических, клинических и инструментальных параметров авторы разработали алгоритм тактики хирургического лечения пациентов с тандем-стенозами шейного и пояснично-крестцового отделов позвоночника, базирующийся на факторах, которые влияют на клинический исход: анамнестических данных (длительности заболевания), особенностях принятой хирургической тактики (первичности отдела позвоночника при вмешательстве, объеме декомпрессии, периоде между этапами операций). При анализе данных современной литературы установлено, что большинство исследований о результатах лечения пациентов с тандем-стенозами позвоночного канала являются ретроспективными [13,17,21,22] или описывают отдельные клинические случаи [12,23,24].…”
Section: Discussionunclassified
“…Recently, treatment with CTLTSS has been reported (95). Some surgeons have applied simultaneous surgery to all lesions and reported improvement without complications (95).…”
Section: Surgical Strategy For Tss With Thssmentioning
confidence: 99%
“…MIOM has been widely used in clinical practice due to its great advantages. [25][26][27] More and more studies have reported that applying MIOM to TSS surgeries can effectively prevent spinal cord injury, and thus lead to better prognosis.…”
Section: Multimodality Intraoperative Monitoring (Miom)mentioning
confidence: 99%